Comparative studies of technological evolution - Chesbrough, Henry William; Burgelman, Robert A. (Research on technological innovation, management and policy, 2001)
This volume provides a collection of cross-country analysis of innovation, showing that the effects of innovation upon firms vary from one country to another. Incumbents perish in one country, while they thrive in the same industry in another country. Startups thrive in response to new technological breakthroughs in one country and struggle in another country. Drawing upon studies of semiconductors, disk drives and biotechnology, and examining institutions such as patent systems and venture capital, this volume takes issue with predictions of convergence, and convincingly demonstrates the multiple paths that technologies and innovations can follow.